APLIKASI MODEL MEAN REVERSION DENGAN MUSIMAN DALAM MENENTUKAN NILAI KONTRAK OPSI TIPE EROPA PADA HARGA KOMODITAS KAKAO - DEWI, IDA AYU PUTU CANDRA; DHARMAWAN, KOMANG; ASIH, NI MADE (E-Jurnal Matematika; Vol 6 No 4 (2017), 2017)
Many literatures explain that commodity prices tend to follow the pattern of Mean Reversion models, commodity prices are controlled by seasonal supplies resulting in price fluctuations. To overcome the risk of fluctuations in the price, an investor can hedge with option contracts. The purpose of this research was to know the application of Mean Reversion model with seasonal in determining the value of European option contract from commodity ,by estimating the parameters and simulating the model in order to get the value of European option contract. Thus, the values of the options obtained with the model was compared with the value of the options calculated by the Black-Scholes model. The results of this study indicated that the value of contract option of Mean Reversion model with seasonal value was lower than the Black-Scholes model.